Chemoprevention of preneoplastic liver foci development by dietary mushroom Agaricus blazei Murrill in the rat - Pinheiro, F.; Faria, R. R.; de Camargo, JLV; Spinardi-Barbisan, ALT; de Eira, A. F.; Barbisan, L. F. (Elsevier B.V., 2003)
The chemopreventive potential of an Agaricus blazei (Ab) Murrill mushroom meal was investigated in a medium-term rat liver carcinogenesis assay. Male Wistar rats initiated for hepatocarcinogenesis with diethylnitrosamine (DEN, 200 mg/kg i.p.) were fed during a 6-week period with the dry powdered mushroom strains Ab 29 or 26, each one with opened (OB) or closed basidiocarp (CB), mixed at 10% level in a basal diet. All experimental animals and controls were subjected to partial hepatectomy at week 3 and killed at week 8. Chemopreventive activity of the mushroom meal was observed for the Ab 29 (OB and CB) and Ab 26 (CB) strains in terms of the number of putative preneoplastic altered foci of hepatocytes which express either the enzyme glutathione S-transferase, placental form (GST-P+) or the transforming growth factor-alpha, and for the Ab 29 (OB) and Ab 26 (CB) strains on the size of GST-P-divided by foci. This was associated with inhibition of foci cell proliferation in the animals fed the Ab 29 (013) and Ab 26 (CB) strains. The results suggest that the protective influence of the Ab meal against the DEN potential for rat liver carcinogenicity depends on both the strain and period of mushroom harvest. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Agaricus blazei Murrill; chemoprevention; liver carcinogenesis